Development of the MDS Model to Support Students’ Learning Management - Sa'diyah, Rika; Anam, Moh Khoirul; Ichsan, Ilmi Zajuli (Pedagonal : Jurnal Ilmiah Pendidikan, 2024)
It is very important to manage student learning so that lectures run well. One effort that can be made is to improve learning management capabilities. Developing a learning model, in this case, the managing, drawing, searching (MDS) model, could be an option for development. This research aims to develop an MDS model for use with students. The method used is research and development (RD) using the ADDIE model approach. The results of this research show that there are three stages of the MDS model, namely manage, which is the stage of problem management that will be discussed by students. The second stage is to describe the problem to be solved along with the solution. The third stage is searching, namely the stage of finding facts related to the solution to the problem. The results of the validation of the MDS model show very valid results by expert 1 with a score of 3.70, and expert 2 with a score of 3.90, which can be interpreted as the MDS model being suitable for use in learning. This research concludes that the MDS model can be used in learning to improve learning management capabilities.